Antipyretic Activity of The Aqueous Extract of Cumin (Cuminum cyminum L.) with Yeast Induced Pyrexia in Female Rats. - Awatif M. Al-Saaedi; Ihsan Hameed khudhair (University of Thi-Qar Journal of Science, 2021)
Abstract— Cumin (Cuminum cyminum L.) is one of the important aromatic plants that is used as an antipyretic in folk medicine. This study aims to evaluate the antipyretic activity of the aqueous extract C. cyminum seeds using the brewer's yeast induced pyrexia method in female rats. Twenty-five adult female rats were divided into five groups (n=5). The first was normal control that only orally received 1 ml of distilled water. Pyrexia was induced in the remaining groups by injection of 30% yeast suspension (10 mg/kg). Two groups of the pyretic animals were set as negative control and positive control groups that were orally treated with 1 ml of distilled water and intraperitoneal injected with Aspirin 100 mg/kg, respectively. The fourth and fifth groups were orally received 200 and 400 mg/kg of the aqueous extract of C. cyminum seeds, respectively. Rectal temperature was significantly (P ≤ 0.05) decreased in the animal groups treated with Aspirin and C. cyminum extract at both doses when it was measured after 1 h. of drug administration.